PENGARUH PERCERAIAN TERHADAP TUMBUH KEMBANG ANAK DALAM KELUARGA (Studi Kasus Di Desa Tertek Dusun Jombangan Kecamatan Pare) - Debi Defura; Awal Mukmin (Institut Agama Islam Hasanuddin Pare, 2025)
This study discusses the Influence of Divorce on Child Development in Families that occurred in Tertek Hamlet, Jombangan Village, Pare District. The purpose of this study was to determine the influence of divorce on child development and how to overcome these impacts. With the aim of determining the various Influences of Divorce on Child Development in Families in Tertek Village, Jombangan Hamlet. The type of research used in this study is Field Research, which is an event of data in the field. The results of this study are: first, Divorce can have a significant impact on child development. Children who experience parental divorce tend to experience stress, confusion, and emotional changes that can affect their mental and social well-being. In addition, divorce can also affect the relationship between children and their parents, damage family stability, and affect children's daily lives in terms of the security, attention, and support they receive. Second, the methods used by parents to help children overcome the impact of divorce are by providing emotional support, open communication, and maintaining children's mental health. Emotional support from parents can help children feel heard, understood, and loved in the difficult situation of divorce. Open communication between parents and children is also important to allow children to express their feelings, understand the situation better, and feel more connected to their parents. In addition, maintaining children's mental health by paying attention to their psychological and emotional needs can help children cope with the psychological impact of divorce.